Plz answer this confusing A.P. problem...!!

Asked by pulkithere1 | 26th Nov, 2010, 05:38: PM

Expert Answer:

Dear student,
 
given: a+(p-1)d = x --------(1)
         a+(q-1)d = y -------(2)
           a+(r-1)d = z   -------(3)
 
now consider equation (1) - (2) and (2) - (3)
 
so (p-q)d = x - y  and (q-r)d = y - z
 
equating value of d,
(x - y)/(p -q) = (y - z)/(q - r)
(x - y)(q - r) = (y - z)(p - q)
 
x(q -r) - y(q - r) = y(p - q) - z(p-q)
 
x(q -r) + y(r - p) + z(p-q) =0
 
We hope this clarifies your query,
regards,
Team Topper Learning
 

Answered by  | 27th Nov, 2010, 10:46: AM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.